Strategic Outsourcing and Service Delivery at the Kenya Revenue Authority (KRA) - Sawe, Titus; Juma, Dennis (Journal of Business and Strategic Management, 2025)
Purpose: The study’s main objective will be to analyze the impact of strategic outsourcing on KRA’s service delivery, with specific objectives focusing on ICT outsourcing, facilities management, customer support, marketing, and research and development. The study is grounded on the Resource-Based View (RBV) and Transaction Cost Economics (TCE) theories, which provide a framework for understanding how outsourcing enhances efficiency and reduces costs. Methodology: A cross-sectional survey design will be employed, targeting KRA employees involved in outsourced functions, including ICT, facilities management, and customer support. A stratified random sampling technique will be used to select 306 respondents from a target population of 1,500 employees. Primary data will be collected using structured questionnaires, and both descriptive statistics (mean, standard deviation, percentages, and graphs) and inferential statistics (correlation and regression analysis) are used for data analysis. Findings: The study findings indicate that ICT outsourcing, facilities management outsourcing, outsourced customer support services, outsourced marketing, and outsourced research and development do not significantly enhance the efficiency of KRA service delivery. Unique Contribution to Theory, Policy and Practice: This study contributes to theory by expanding the understanding of strategic outsourcing in public sector institutions. It informs policy by providing insights into optimizing outsourcing practices for enhanced service delivery at KRA. In practice, it offers actionable recommendations for improving efficiency and accountability in outsourcing arrangements, benefiting both the public sector and service providers.